Characterization of the Microbiome along the Gastrointestinal Tract of Growing Turkeys - Wilkinson, Toby J.; Cowan, A. A.; Vallin, H. E.; Onime, L. A.; Oyama, Linda B.; Cameron, S. J.; Gonot, Charlotte; Moorby, J. M.; Waddams, K.; Theobald, V. J.; Leemans, D.; Bowra, S.; et al. (Frontiers in Microbiology, 2017)
The turkey microbiome is largely understudied, despite its relationship with bird health and growth, and the prevalence of human pathogens such as Campylobacter spp. In this study we investigated the microbiome within the small intestine (SI), caeca (C), large intestine (LI) and cloaca (CL) of turkeys at 6, 10 and 16 weeks of age. Eight turkeys were dissected within each age category and the contents of the SI, C, LI and CL were harvested. 16S rDNA based QPCR was performed on all samples and samples for the 4 locations within 3 birds/age group were sequenced using ion torrent-based sequencing of the 16S rDNA. Sequencing data showed on a genus level, an abundance of Lactobacillus, Streptococcus and Clostridium XI (38.2, 28.1 and 13.0% respectively) irrespective of location and age. The caeca exhibited the greatest microbiome diversity throughout the development of the turkey. PICRUSt data predicted an array of bacterial function, with most differences being apparent in the caeca of the turkeys as they matured. QPCR revealed that the caeca within 10 week old birds, contained the most Campylobacter spp. Understanding the microbial ecology of the turkey gastrointestinal tract is essential in terms of understanding production efficiency and in order to develop novel strategies for targeting Campylobacter spp.